Harmony Family Communication (Hita Sukhaya) In Buddhist Perspective - Marjianto, Ramdan Pelana, Rudi Hartono (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research aims to reveal the relationship between the effectiveness of interpersonal communication and the hita sukhaya family and to reveal the factors affecting hita sukhaya family. The approach used is qualitative approach. The techniques used to collect the data are interview, observation, and documentation. The result of the study shows that interpersonal communication in hita sukhaya family has different characteristics between one and another. Some characteristics of an effective interpersonal communication in hita sukhaya family are openness, empathy, supportness, positiveness, and equality. An effective interpersonal communication can be materialized in a joyful atmosphere, full of understanding, full of compassion one and other so that it can emerge the intimate and cheerful atmosphere. To achieve hita sukhaya family, a family should have an equal conviction, an equal morality, an equal generosity, and an equal wisdom. A religious conviction, an effective communication, an equal between rights and responsibility, and economic factors are the parts that cannot be separated one and another to achieve a harmony or hita sukhaya family